DEVIATIONS OF MODERN PUBLIC SPEECH: OBSCENE VOCABULARY (BASED ON BLOGS ON CENSOR.NET) - Barchuk, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Aim. The article is devoted to the study of the peculiarities of modern Ukrainian public speech based on the texts of the bloggers of the online publication Tsenzor.net. The deviations are object of analysis in journalistic texts, in particular the conventionality and peculiarities of the use of obscene vocabulary. Traditionally, language deviations are considered as a communicative failure or mistake. The work defines a new aspect of the interpretation of deviations as a means of achieving a communicative goal, realizing the intention of the sender, revealing the content and emotionally and axiological directing the discourse. The reasons for the use of obscene vocabulary in public speech, its appropriateness, functional boundaries and ethnic features of use are substantiated. The prospects and tasks of the development of Ukrainian public speech are defined. Methods. The key research method is descriptive. At the same time, a comparative-typological analysis of the denotative-connotative, emotional-evaluative, cultural-ethical meaning of obscene lexemes and their functional status was used. The contextual analysis made it possible to establish the background and conditionality of the functional-semantic load of intentional deviations as text-creating tools. Results. The study of the language of bloggers revealed that language deviations are a typical feature of texts in the modern media space. It was determined that part of the deviations is a consequence of the dynamism of the information field, due to gaps in the formation of linguistic personality, as well as a low level of requirements for language culture. On the other hand, part of linguistic, first of all lexical, deviations is a conscious choice of the authors, in particular the use of obscene words. The level of stylistic marking of obscene vocabulary, which the authors use directly, euphemizing or presenting it already as jargon and slang, has been established. The appropriateness of the use of deviant vocabulary from the point of view of the perspective of the development of Ukrainian public speech is determined. Originality. The author's concept of lexical deviations as a means of achieving a communicative goal is substantiated. The model for describing obscene vocabulary in public speech is proposed based on a holistic analysis of the text, its communicative and pragmatic features, and the conditions for the appearance of lingual deviations. Practical significance. Research material can be used to study the stylistically marked components of the author's discourse within the course of linguistic analysis of the text. The conclusions and generalizations will contribute to the elaboration of the foundations of the development of both public speech and the Ukrainian lingual identity.